Randomized double-blind clinical study in patients with COVID-19 to evaluate the safety and efficacy of a phytomedicine (P2Et) - Urueña, Claudia; Ballesteros-Ramírez, Ricardo; Gomez-Cadena, Alejandra; Barreto, Alfonso; Prieto, Karol; Quijano, Sandra; Aschner, Pablo; Martínez, Carlos; Zapata-Cardona, Maria I.; El-Ahanidi, Hajar; Jandus, Camilla; Florez-Alvarez, Lizdany; et al. (Frontiers in Medicine, 2022)
Background: It has been proposed that polyphenols can be used in the development of new therapies against COVID-19, given their ability to interfere with the adsorption and entrance processes of the virus, thus disrupting viral replication. Seeds from Caesalpinia spinosa, have been traditionally used for the treatment of inflammatory pathologies and respiratory diseases. Our team has obtained an extract called P2Et, rich in polyphenols derived from gallic acid with significant antioxidant activity, and the ability to induce complete autophagy in tumor cells and reduce the systemic inflammatory response in animal models. Methods: In this work, a phase II multicenter randomized double-blind clinical trial on COVID-19 patients was designed to evaluate the impact of the P2Et treatment on the clinical outcome and the immunological parameters related to the evolution of the disease. The Trial was registered with the number No. NCT04410510*. A complementary study in an animal model of lung fibrosis was carried out to evaluate in situ lung changes after P2Et in vivo administration. The ability of P2Et to inhibit the viral load of murine and human coronaviruses in cellular models was also evaluated. Results: Patients treated with P2Et were discharged on average after 7.4 days of admission vs. 9.6 days in the placebo group. Although a decrease in proinflammatory cytokines such as G-CSF, IL-15, IL-12, IL-6, IP10, MCP-1, MCP-2 and IL-18 was observed in both groups, P2Et decreased to a greater extent G-CSF, IL-6 and IL-18 among others, which are related to lower recovery of patients in the long term. The frequency of T lymphocytes (LT) CD3+, LT double negative (CD3+CD4-CD8-), NK cells increased in the P2Et group where the population of eosinophils was also significantly reduced. In the murine bleomycin model, P2Et also reduced lung inflammation and fibrosis. P2Et was able to reduce the viral replication of murine and human coronaviruses in vitro, showing its dual antiviral and anti-inflammatory role, key in disease control. Conclusions: Taken together these results suggest that P2Et could be consider as a good co-adjuvant in the treatment of COVID-19. *(https://clinicaltrials.gov/ct2/show/NCT04410510)